The Nazareth Scotch: dance uniform as admonitory infrapolitics for an eikonic Zion City in early Union Natal - Papini, R. (Southern African Humanities, 2002)
Uniform has been called a 'fetish object which through ritual organisation helps nationalism's 'theatrical performance of invented community' (McClintock, A. 1995: 374-375). In both male and female sectors of the Nazareth Baptist Church's holy dances today, an overwhelming majority outfitted in neotraditional 'IsiZulu' uniform gives onlookers the impression of a standard-bearing ecclesiastical nationalism - a 'Zulu Christian' church. Drawing all ages, the men's IsiZulu typically outnumbers by five to one the other male uniform - a syncretic ensemble known as 'the Scotch', whose more demanding dance means that men seldom remain in it beyond their twenties. Inspired by perspectives from postcolonial theory, this essay asks how, for an African-initiated church whose indigenising or inculturative character is most manifest in its dance uniforms, it might be possible to read this apparently anomalous Western derivation. If material culture is a communicative system (Eicher 1995), what meaning might a 'fetishistic' sacramental garb such as the Scotch hold for wearers and watchers - as sacred dance apparel, what prophetic hierography encode - in the drama of ritual liminality called by Victor Turner (1975: 111) 'an exteriorised mystical way'?